Minocycline promotes the generation of dendritic cells with regulatory properties - Kim, Narae (Oncotarget, 2016)
Minocycline, which has long been used as a broad-spectrum antibiotic, also exhibits non-antibiotic properties such as inhibition of inflammation and angiogenesis. In this study, we show that minocycline significantly enhances the generation of dendritic cells (DCs) from mouse bone marrow (BM) cells when used together with GM-CSF and IL-4. DCs generated from BM cells in the presence of minocycline (Mino-DCs) demonstrate the characteristics of regulatory DCs. Compared with control DCs, Mino-DCs are resistant to subsequent maturation stimuli, impaired in MHC class II-restricted exogenous Ag presentation, and show decreased cytokine secretion. Mino-DCs also show decreased ability to prime allogeneic-specific T cells, while increasing the expansion of CD4(+)CD25(+)Foxp3(+) T regulatory cells both in vitro and in vivo. In addition, pretreatment with MOG35-55 peptide-pulsed Mino-DCs ameliorates clinical signs of experimental autoimmune encephalitis induced by MOG peptide injection. Our study identifies minocycline as a new pharmacological agent that could be potentially used to increase the production of regulatory DCs for cell therapy to treat autoimmune disorders, allergy, and transplant rejection.